The Relationship between Emotional, Social, Cultural, Spiritual Intelligence and EFL Teachers’ Teaching Effectiveness - Nikoopour, Jahanbakhsh; Esfandiari, Nadimeh (Journal of Language Teaching and Research, 2017)
The present study attempted to investigate the relationship between EFL teachers’ emotional, social, cultural, spiritual intelligence and their teaching effectiveness in EFL contexts. Teaching effectiveness was investigated as perceived by EFL teachers, observers and learners based on a data-triangulated procedure. A total of 126 EFL teachers, 266 learners and 31 EFL observers selected randomly from various educational districts in Tehran participated in the study. The EFL teachers were required to answer self-report questionnaires of Teaching Effectiveness Scale (TES), Emotional Intelligence Questionnaire (TEIQue), Cultural Intelligence Scale (CQS), Tromsø Social Intelligence Scale (TSIS) and Integrated Spiritual Intelligence Scale (ISIS) respectively. The EFL observers and learners were also required to answer Teaching Effectiveness Scale (TES) to reveal their perception of their teachers’ teaching effectiveness. The study revealed that among EFL teachers, there was a significant correlation between teaching effectiveness and TEQ, but the correlation between teaching effectiveness and the three other types of intelligence (SQ, CQ, & SPQ) was not significant. The three groups of participants (teachers, observers, and learners) showed a significant difference in their perception of effective teaching. In further analysis, gender made a significant difference in TEQ, but female and male EFL teachers did not show a significant difference in their CQ, SQ, SPQ and effective teaching. University degree caused a significant difference in SQ and TEQ, but not in TE, SPQ and CQ. However, teaching experience and age made a significant difference in all four variables under the study.